2019
DOI: 10.1007/s41978-019-00038-y
|View full text |Cite
|
Sign up to set email alerts
|

‘Relaxing Way to Spend a Day’ or ‘Best Way to Keep Fit and Healthy’. Comparison of Leisure Experiences in Rambling and Nordic Walking and their Contributions to Well-Being

Abstract: The increasing academic interest in walking for heath has paid limited attention to Nordic walking. This paper investigates the growing popularity of Nordic walking as a leisure activity in the United Kingdom and its contribution to well-being. It investigates the similarities and differences in leisure experiences between Nordic walking and rambling. Twelve Nordic walkers and thirteen Ramblers partook in semi-structured interviews at various locations in the United Kingdom. The interviews were analysed themat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Other research has reported that, for individuals with severe mental illness (SMI), and those with low self‐esteem and confidence, in particular, social support from others with SMI facilities the formation of feelings of togetherness that reinforces shared identities (Crone, 2007; Quirk et al., 2020; Soundy et al., 2012, 2015), having a positive effect on participation. There is, however, the possibility of reverse causality, with PA being a normalising experience through providing an environment and opportunities for socialisation (Mourão et al., 2019; Zurawik et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has reported that, for individuals with severe mental illness (SMI), and those with low self‐esteem and confidence, in particular, social support from others with SMI facilities the formation of feelings of togetherness that reinforces shared identities (Crone, 2007; Quirk et al., 2020; Soundy et al., 2012, 2015), having a positive effect on participation. There is, however, the possibility of reverse causality, with PA being a normalising experience through providing an environment and opportunities for socialisation (Mourão et al., 2019; Zurawik et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al [20] reported a significant reduction in shoulder problems among women with breast cancer immediately after the Nordic walking intervention. In contrast, the psychological and social benefits of the activity have attracted recent attention, which is still very limited [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…the growing academic literature on the social aspects of physical activity, including walking, has acknowledged that adults are more likely to become active and maintain an active lifestyle if they have opportunities to interact, communicate with others, and share experiences [22,24,25]. Moreover, interactions of individuals who consider themselves as a part of a group with other members generate a sense of belonging and identity with a particular group.…”
Section: Introductionmentioning
confidence: 99%